An Analysis of the Purposes of Cost Accounting in Large U.S. Cities. (March 2015) - Mohr, Zachary T.
Abstract : Research on U.S. government cost accounting has received little attention in recent years. This article analyzes four of the main reasons why large cities use cost accounting: performance management, grant overhead recovery, rate setting, and cost management to reduce fiscal stress. Using a cross section of 81 cities with populations over 100, 000 people, it finds that cost allocation plans are correlated with lower fund balances and are positively correlated with enterprise expenditures. These correlations suggest that the use of cost accounting is related to fiscal stress and rate setting. Research limitations and policy implications are addressed.